9x-96=6x-9

Simple and best practice solution for 9x-96=6x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-96=6x-9 equation:


Simplifying
9x + -96 = 6x + -9

Reorder the terms:
-96 + 9x = 6x + -9

Reorder the terms:
-96 + 9x = -9 + 6x

Solving
-96 + 9x = -9 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-96 + 9x + -6x = -9 + 6x + -6x

Combine like terms: 9x + -6x = 3x
-96 + 3x = -9 + 6x + -6x

Combine like terms: 6x + -6x = 0
-96 + 3x = -9 + 0
-96 + 3x = -9

Add '96' to each side of the equation.
-96 + 96 + 3x = -9 + 96

Combine like terms: -96 + 96 = 0
0 + 3x = -9 + 96
3x = -9 + 96

Combine like terms: -9 + 96 = 87
3x = 87

Divide each side by '3'.
x = 29

Simplifying
x = 29

See similar equations:

| 2/3x^-1/3=0 | | an-7an-1+10an-2=4n | | (2k^2-4k+5)=0 | | 1y+3-1y=3 | | -3+6-3x+7x=14 | | ln*lnx/2-lnx0 | | 10m=-36+86 | | 3r-72=25 | | -13y=-13 | | 15=5/3x-10 | | 1y+12-1y=3 | | 95-2x=16x+19 | | 18-2(-4+2)= | | 6x-3x+7=-3 | | z^8=2 | | 7(8+6p)=392 | | 3x^3+9x^2-120x=0 | | z^5=-2i | | 84=7(-4p+8) | | 10x^4-1=0 | | 5550000x+2085000000=3056890000-15000000x | | -3.5x+4.2=1.9x-2.7 | | 7(2-2p)=-98 | | 224=-8(7p-7) | | 3(1+8p)=-93 | | f-4=6f+25 | | 3m(x+m+2+3x+2m)= | | 3ab^-5/3^-1a^-3b4 | | x+(x-48)+(3*(x-48))=898 | | -4/-81 | | 2X^5+X-5=0 | | 5/(-5/4) |

Equations solver categories